Sexual Health Dysfunction After Radiotherapy for Gynecological Cancer: Role of Physical Rehabilitation Including Pelvic Floor Muscle Training - Amelia Barcellini; Mattia Dominoni; Mattia Dominoni; Francesca Dal Mas; Francesca Dal Mas; Helena Biancuzzi; Sara Carla Venturini; Barbara Gardella; Barbara Gardella; Ester Orlandi; Kari Bø; Kari Bø (Frontiers in Medicine, 2022)
IntroductionThe present study aims to describe: 1. How the side effects of radiotherapy (RT) could impact sexual health in women; 2. The effectiveness of physical rehabilitation including pelvic floor muscle training (PFMT) in the management of sexual dysfunction after RT.Materials and MethodsSearch keys on PubMed, Web of Science, Scopus, PEDro, and Cochrane were used to identify studies on women treated with radical or adjuvant RT and/or brachytherapy for gynecological cancers with an emphasis on vulvo-vaginal toxicities and PFMT studies on sexual dysfunction for this group of women.ResultsRegarding the first key question, we analyzed 19 studies including a total of 2,739 women who reported vaginal dryness, stenosis, and pain as the most common side effects. Reports of dosimetric risk factors and dose-effect data for vaginal and vulvar post-RT toxicities are scant. Only five studies, including three randomized controlled trials (RCTs), were found to report the effect of PFMT alone or in combination with other treatments. The results showed some evidence for the effect of training modalities including PFMT, but to date, there is insufficient evidence from high-quality studies to draw any conclusion of a possible effect.ConclusionsGynecological toxicities after RT are common, and their management is challenging. The few data available for a rehabilitative approach on post-actinic vulvo-vaginal side effects are encouraging. Large and well-designed RCTs with the long-term follow-up that investigate the effect of PFMT on vulvo-vaginal tissues and pelvic floor muscle function are needed to provide further guidance for clinical management.